2020
DOI: 10.1159/000510534
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Potential Hub Genes and Therapeutic Drugs in Malignant Pleural Mesothelioma by Integrated Bioinformatics Analysis

Abstract: <b><i>Introduction:</i></b> Malignant pleural mesothelioma (MPM) is closely linked to asbestos exposure and is an extremely aggressive tumor with poor prognosis. <b><i>Objective:</i></b> Our study aimed to elucidate hub genes and potential drugs in MPM by integrated bioinformatics analysis. <b><i>Methods:</i></b> GSE42977 was download from the Gene Expression Omnibus (GEO) database; the differentially expressed genes (DEGs) with adj.<i&… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 70 publications
0
6
0
Order By: Relevance
“…BAP1 is a histone deubiquitination enzyme encoded by genes. BAP1 is an important tumor suppressor gene encoded in the 21.1 region of the short arm of chromosome 3 (17) and can significantly increase the stability of the KLF5 protein. Righi et al (18) established that the most commonly mutated genes in malignant mesothelioma genome research results are BAP1, NF2 and CDKN2A/B.…”
Section: Introductionmentioning
confidence: 99%
“…BAP1 is a histone deubiquitination enzyme encoded by genes. BAP1 is an important tumor suppressor gene encoded in the 21.1 region of the short arm of chromosome 3 (17) and can significantly increase the stability of the KLF5 protein. Righi et al (18) established that the most commonly mutated genes in malignant mesothelioma genome research results are BAP1, NF2 and CDKN2A/B.…”
Section: Introductionmentioning
confidence: 99%
“…proved through bioinformatics that the survival rate of MPM cases in the KIF20A high expression group was significantly lower than that of the low expression group. In addition, as indicated by the analysis of Cox regression factors, as opposed to MPM cases in the low expression group, the high expression of the mentioned genes is a risk factor for prognosis ( 35 ). Furthermore, the present study proved that the survival time of MPM cases with high KIF20A expression was significantly shorter than that of the low expression group, complying with the results of this article.…”
Section: Discussionmentioning
confidence: 99%
“…We have found both TEK and ANGPT1 are downregulated in MPM. Zhang et al (2020) [12] showed that CXCL8/IL8, PPARG, ADIPOQ, and IL6 are upregulated in malignant pleural mesothelioma. But we have found from our analyses that these genes are downregulated in MPM.…”
Section: Discussionmentioning
confidence: 99%
“…These key genes can be used as biomarkers and can be utilized for early diagnosis, survival prediction, drug target identification, and drug response observation [5][6][7][8][9][10][11]. Bioinformatics analyses have been employed to identify important genes and pathways involved in the disease process of malignant pleural mesothelioma [12][13][14]. Bioinformatics approach has also identified upregulation of spliceosomal genes, especially SF3B1 [15] and haploinsufficiency of BAP1 gene [16] are associated with MPM.…”
Section: Original Articlementioning
confidence: 99%